Neoadjuvant Therapy in Stage II/III Rectal Cancer: A Retrospective Study in a Disparate Population and the Effect on Survival. Issue 10 (October 2021) - Gan, Tong; Chen, Quan; Huerta, Carlos T.; Huang, Bin; Evers, B. Mark; Patel, Jitesh A.
Abstract : BACKGROUND: Kentucky has one of the highest rectal cancer incidences in the United States. High poverty rates have led to poor insurance coverage and inadequate access to care. The treatment of locally advanced rectal cancer utilizes a multimodal regimen requiring regular access to expert care. The rate of receipt of neoadjuvant therapy in Kentucky is unknown. OBJECTIVE: This study aimed to evaluate the rate and factors associated with the receipt of neoadjuvant therapy for localized advanced rectal cancer in Kentucky and the effect on overall survival. DESIGN: This is a retrospective database review. SETTINGS: This study was conducted by utilizing the Kentucky Cancer Registry at an academic center. PATIENTS: All patients diagnosed with stage II/III rectal adenocarcinoma from 2005 to 2015 in the Commonwealth of Kentucky were included. MAIN OUTCOME MEASURES: The primary outcomes measured were the factors associated with nonreceipt of neoadjuvant therapy and overall survival. RESULTS: Of 1896 patients, only 46.8% received neoadjuvant therapy. Factors associated with not receiving neoadjuvant therapy included older age, female sex, low education level, high poverty level, and treatment at nonacademic centers. Survival analysis demonstrated significantly improved survival in patients receiving neoadjuvant therapy compared with other treatment regimens. LIMITATIONS: This study was limited by the retrospective nature of the review and by unmeasured confounders. CONCLUSIONS: Our study was the first to evaluate the factors behind the low rates of neoadjuvant therapy for locally advanced rectal cancer in Kentucky. Neoadjuvant therapy in this population is beneficial for survival; efforts should be made in policy and education with focus on older patients, female patients, and treatment at nonacademic centers. Centralization of rectal cancer care improves outcomes, but we must be aware of the effect it may have on disparate populations with poor access. See Video Abstract at http://links.lww.com/DCR/B596 . TERAPIA NEOADYUVANTE EN EL MANEJO DEL CÁNCER DE RECTO EN ESTADIO II / III: UN ESTUDIO RETROSPECTIVO EN UNA POBLACIÓN DISPAR Y EL EFECTO EN LA SUPERVIVENCIA: ANTECEDENTES: El estado de Kentucky tiene una de las mayores incidencias de cáncer de recto en los EE. UU. Debido a una alta tasa de pobreza, el porcentaje de la población que cuenta con seguro de salud, es muy limitado, y por lo tanto el acceso a una atención de alto nivel es muy bajo. El tratamiento del cáncer de recto localmente avanzado, es multidisciplinario, lo que exige acceso y disponibilidad a un grupo experto. Se desconoce la tasa de pacientes que reciben terapia neoadyuvante en Kentucky. OBJETIVO: Establecer la tasa y los factores asociados con el uso de terapia neoadyuvante en el tratamiento del cáncer de recto localmente avanzado en Kentucky, y su efecto en la supervivencia global. DISEÑO: Revisión retrospectiva de una base de datos. ESCENARIO: Este estudio se llevó a cabo utilizando el Registro de Cáncer de Kentucky en un centro académico. PACIENTES: Se incluyen todos los pacientes diagnosticados con adenocarcinoma de recto, de la Mancomunidad (Commonwealth) de Kentucky, en estadio II / III entre 2005 y 2015. PRINCIPALES MEDIDAS DE RESULTADO: Establecer los factores asociados con el hecho de no recibir terapia neoadyuvante; y establecer la supervivencia global. RESULTADOS: De 1896 pacientes evaluados, solo el 46, 8% recibió terapia neoadyuvante. Los factores asociados, para no haber recibido terapia neoadyuvante fueron: la edad avanzada, sexo femenino, bajo nivel educativo, alto nivel de pobreza y tratamiento en centros no académicos. El análisis de la supervivencia mostró una supervivencia significativamente mejor en los pacientes que recibieron terapia neoadyuvante en comparación con otros esquemas de tratamiento. LIMITACIONES: Revisión retrospectiva, factores de confusión no medidos. CONCLUSIONES: Nuestro estudio ha sido el primero en evaluar los factores determinantes de las bajas tasas de terapia neoadyuvante para el tratamiento del cáncer de recto localmente avanzado en Kentucky. La terapia neoadyuvante mejora y favorece la supervivencia en esta población, por lo tanto se deben hacer esfuerzos en las políticas de salud, así como en educación, enfocados a los pacientes mayores, pacientes femeninas y tratamiento en centros no académicos. El centralizar la atención del cáncer de recto, mejora los resultados, pero debemos ser conscientes del efecto que puede tener en poblaciones desiguales económicamente, con acceso deficiente a la posibilidad de recibir atención de alto nivel. Consulte Video Resumen en http://links.lww.com/DCR/B596 .